A coating material for cemented carbide and preparation method thereof
By using AlN@Cu micropowder in high-entropy alloy coating materials, and introducing copper coating and uniform copper layer using surface modifiers, the problem of ceramic particles forming a dense coating during laser cladding is solved, and a coating material with high wear resistance and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411823787.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Existing high-entropy alloy coating materials are difficult to meet wear resistance requirements in high-efficiency mold applications, and ceramic particles are difficult to form a continuous dense coating during laser cladding, resulting in insufficient performance and reduced corrosion resistance.
AlN@Cu micropowder is used as the coating material, and copper coating is introduced on the surface of the aluminum nitride powder through a surface modifier to improve the wetting and density of aluminum nitride particles, and the bond toughness and corrosion resistance of the coating are enhanced through a uniform copper layer.
High wear resistance and corrosion resistance of high entropy alloy coating materials are achieved, and the surface quality and designability of cemented carbide products are improved through dense coating structure and uniform copper layer.
Smart Images

Figure CN119287362B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface engineering, and in particular relates to a coating material for cemented carbide and a preparation method thereof. Background Art
[0002] Cemented carbide is a material with tungsten carbide as the main component and a small amount of bonding metal added. It has extremely high strength and hardness and is widely used in the fields of molds and tool materials. However, in some working conditions, such as drawing dies and cold forging dies, the surface is subjected to long-term friction and wear and contact with various lubricating media, which can easily cause surface wear and corrosion. The molding process of cemented carbide products is complicated, and the decline in surface quality will directly affect the quality of the product, while frequent mold replacement will increase production costs. Laser cladding is an advanced material surface engineering technology that uses a high-energy laser beam to melt and deposit coating materials in the form of powder or wire on the surface of the substrate to form a layer of coating that is metallurgically bonded to the substrate. By adjusting the material ratio of the coating, different surface properties are given to cemented carbide, effectively improving the surface quality of cemented carbide products and the designability of the products.
[0003] High entropy alloy is an alloy composed of five or more main elements. Under the combined influence of high entropy effect, lattice distortion effect, hysteresis diffusion effect and "cocktail" effect, high entropy alloy exhibits excellent properties, such as high hardness and high wear resistance, and is an excellent raw material for cemented carbide coating materials; however, with the development of high-efficiency molds, existing high-entropy alloy-based alloys are gradually unable to meet the wear resistance requirements. In the prior art, by introducing certain ceramic particles into the high-entropy alloy coating material, the wear resistance of the coating can be improved to a certain extent; however, the melting point of ceramic particles is extremely high. In the laser cladding molten pool, the ceramic particles still exist as free hard phases, and it is difficult to form a continuous and dense coating with the cladding layer. A large number of defects and stress concentration are easily generated between the ceramic particles and the coating substrate, resulting in insufficient performance of the ceramic particles and the coating substrate, making it difficult to fully exert the improvement in wear resistance, and it is also easy to cause a decrease in corrosion resistance. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a coating material for cemented carbide and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A coating material for cemented carbide consists of the following components: 17-23wt% of AlN@Cu micropowder and 3.5-4.5wt% of cladding aid, with the balance being high entropy alloy powder.
[0007] The AlN@Cu powder is prepared by the following method:
[0008] Step A1: Dissolve dithiothreitol and acetone under nitrogen protection, then add triallylamine and bis(triphenylphosphine)copper chloride and mix well. Control the temperature of the water bath at 40-50°C, stir at 120-150 rpm, and apply 80-110 W / m 2 The reaction time is controlled to be 6.5-8 hours to obtain a surface modifier;
[0009] Furthermore, the feed ratio of triallylamine, dithiothreitol, bis(triphenylphosphine)copper chloride and acetone is 10mmol:17-20mmol:9-13mg:25-35mL, and under the catalysis of bis(triphenylphosphine)copper chloride and initiation of ultraviolet light, dithiothreitol and triallylamine undergo addition reaction to form a macromolecular compound containing hydroxyl groups on the side chain.
[0010] Step A2: dissolving the surface modifier and dimethylacetamide, adding aluminum nitride powder, mixing and standing for 24 hours, then adding copper sulfate solution and ultrasonically dispersing for 15-25 minutes, then adding zinc powder and heating to 60-80°C to react for 20-30 hours, centrifuging and taking the precipitate, washing it with hydrochloric acid and water in turn, and drying to obtain a copper-coated substrate;
[0011] Furthermore, the feed ratio of aluminum nitride powder, surface modifier, copper sulfate, zinc powder and dimethylacetamide is 10g: 0.14-0.18g: 2.7-3.3g: 1.6-2.1g: 30-40mL, the hydroxyl groups on the side chains of the surface modifier macromolecules form hydrogen bonds with the oxygen-containing groups on the surface of the aluminum nitride powder, and are loaded onto the surface of the aluminum nitride powder, and the nitrogen-containing sulfide structure thereof forms a chelating effect to capture the added copper ions, enriching the copper ions on the surface of the aluminum nitride, and then the surface of the aluminum nitride is coated with copper under the reduction of the zinc powder;
[0012] Preferably, the aluminum nitride powder is a micron-sized powder with an average particle size of no more than 20 μm. Small-particle aluminum nitride has a large specific surface area, a high content of surface oxygen-containing groups, and is easier to form a dense coating after laser cladding.
[0013] Step A3: Place the copper-clad substrate in a nitrogen atmosphere furnace, first bake it at 380-440°C for 2.5-3h, then continue to heat it to 820-850°C and bake it for 1-1.3h, and then break it up after cooling in the furnace to obtain AlN@Cu micropowder.
[0014] Preferably, the high entropy alloy powder is one of FeCoNiCrTi alloy powder and FeCoNiCrMn alloy powder.
[0015] Preferably, the particle size of the high entropy alloy powder is 10-60 μm.
[0016] Preferably, the cladding aid is atomized iron powder.
[0017] A method for preparing a coating material for cemented carbide comprises the following steps: mixing various raw materials, dry grinding and dispersing them, and vacuum drying them to obtain the coating material.
[0018] Beneficial effects of the present invention:
[0019] The invention discloses a preparation method of AlN@Cu (copper-coated aluminum nitride) micropowder, which is formed by the addition reaction of dithiothreitol and triallylamine to form a macromolecular compound containing hydroxyl groups on the side chain, i.e., a surface modifier, and the hydroxyl groups on the macromolecular side chain form hydrogen bonds with oxygen-containing groups on the surface of aluminum nitride powder, and are loaded onto the surface of aluminum nitride powder, and the added copper ions are captured by the chelation effect formed by the nitrogen-containing sulfide structure in the molecule, and the copper ions are enriched on the surface of aluminum nitride, and then the surface of aluminum nitride is coated with copper element under zinc powder reduction. Compared with the existing copper-coated ceramic material, the surface modifier plays a bidirectional bridging role, and copper coating is uniformly introduced on the surface of aluminum nitride, which is applied to laser cladding. During coating, the copper layer is used as a wetting material to improve the wettability of the high-melting-point aluminum nitride particles and the high-entropy alloy molten phase, which is beneficial to the full flow of the melt to form a dense coating. The surface modifier is composed of C, N and S as the main elements. After sufficient roasting, the residual impurities are low, and it is not easy to form electrochemical corrosion in the coating, which is significantly helpful for improving the corrosion resistance of the coating. On the other hand, the uniform copper layer acts as a relatively soft connecting material in the coating, which makes the bonding toughness of the hard phase aluminum nitride particles and the high-entropy alloy sintered phase higher. During the friction and wear process, the hard aluminum nitride particles are not easy to fall off to form abrasive particles. Combined with the improvement of the density of the coating, the wear resistance of the coating can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0021] Figure 1 This is a scanning electron microscope image of the AlN@Cu powder prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1, preparation of coating material for cemented carbide, the specific implementation process is as follows:
[0024] (1) Preparation of AlN@Cu powder
[0025] Step A1: Dissolve dithiothreitol and acetone under nitrogen protection, then add triallylamine and bis(triphenylphosphine)copper chloride and mix well. Control the temperature of the water bath at 50°C, stir at 150 rpm, and apply 110 W / m 2 The reaction mixture was irradiated with ultraviolet light and the reaction time was controlled to be 6.5 h. The feed ratio of triallylamine, dithiothreitol, bis(triphenylphosphine)copper chloride and acetone was 10 mmol:20 mmol:13 mg:35 mL. After the reaction was completed, acetone was removed to obtain a surface modifier.
[0026] Step A2: Take the surface modifier and dimethylacetamide and mix them, add aluminum nitride powder and mix them, then let it stand for 24 hours, take copper sulfate to prepare a saturated solution, add the copper sulfate solution and ultrasonically disperse it for 15 minutes, then add zinc powder and heat it to 80°C to react for 20 hours, wherein the feed ratio of aluminum nitride powder, surface modifier, copper sulfate, zinc powder and dimethylacetamide is 10g:0.18g:3.3g:2.1g:40mL, aluminum nitride powder uses Brofos-AlN-W20 type micropowder with an average particle size of 20 microns, finally centrifuge to obtain the precipitate, wash it with hydrochloric acid and water in turn, and obtain the copper-coated substrate after drying.
[0027] Step A3: Place the copper-clad substrate in a nitrogen atmosphere furnace, first bake it at 440°C for 2.5 hours, then continue to heat it to 850°C for 1 hour, and then break it up after cooling in the furnace to obtain AlN@Cu micropowder.
[0028] (2) Preparation of coating materials
[0029] The raw materials are taken according to weight percentage, 17wt% of AlN@Cu micropowder is prepared by this embodiment; 4.5wt% of cladding aid is HT40.37 atomized iron powder; the balance is made up to 100wt% with FeCoNiCrTi high entropy alloy powder, and the particle size distribution is 15-45μm; the raw materials are mixed, added into a grinder for grinding and dispersion, and vacuum dried to obtain a coating material.
[0030] Example 2, preparing a coating material for cemented carbide, the specific implementation process is as follows:
[0031] (1) Preparation of AlN@Cu powder
[0032] Step A1: Dissolve dithiothreitol and acetone under nitrogen protection, then add triallylamine and bis(triphenylphosphine)copper chloride and mix well. Control the temperature in a water bath at 40°C, stir at 120 rpm, and heat at 80 W / m 2The reaction mixture was irradiated with ultraviolet light and the reaction time was controlled to be 8 h. The feed ratio of triallylamine, dithiothreitol, bis(triphenylphosphine)copper chloride and acetone was 10 mmol:17 mmol:9 mg:25 mL. After the reaction was completed, acetone was removed to obtain a surface modifier.
[0033] Step A2: Mix the surface modifier and dimethylacetamide, add aluminum nitride powder and mix, and then stand for 24 hours. Take copper sulfate to prepare a saturated solution, add the copper sulfate solution and ultrasonically disperse for 25 minutes, then add zinc powder and heat to 60°C to react for 30 hours, wherein the feed ratio of aluminum nitride powder, surface modifier, copper sulfate, zinc powder and dimethylacetamide is 10g:0.14g:2.7g:1.6g:30mL, and aluminum nitride powder uses Brofos-AlN-W20 type micropowder with an average particle size of 20 microns. Finally, centrifuge to obtain the precipitate, wash it with hydrochloric acid and water in turn, and dry it to obtain a copper-coated substrate.
[0034] Step A3: Place the copper-clad substrate in a nitrogen atmosphere furnace, first bake it at 380°C for 3 hours, then continue to heat it to 820°C and bake it for 1.3 hours, and then break it up after cooling in the furnace to obtain AlN@Cu micropowder.
[0035] (2) Preparation of coating materials
[0036] The raw materials are taken according to weight percentage, 23wt% of AlN@Cu powder is prepared by this embodiment; 3.5wt% of cladding aid is HT40.37 atomized iron powder; the balance is made up to 100wt% with FeCoNiCrTi high entropy alloy powder, and the particle size distribution is 15-45μm; the raw materials are mixed, added into a grinder for grinding and dispersion, and vacuum dried to obtain a coating material.
[0037] Example 3, preparing a coating material for cemented carbide, the specific implementation process is as follows:
[0038] (1) Preparation of AlN@Cu powder
[0039] Step A1: Dissolve dithiothreitol and acetone under nitrogen protection, then add triallylamine and bis(triphenylphosphine)copper chloride and mix well. Control the temperature of the water bath at 45°C, stir at 120 rpm, and heat at 90 W / m 2 The reaction time was controlled to be 7.5 h, wherein the feed ratio of triallylamine, dithiothreitol, bis(triphenylphosphine)copper chloride and acetone was 10 mmol:18 mmol:12 mg:30 mL. After the reaction was completed, acetone was removed to obtain a surface modifier.
[0040] Step A2: Take the surface modifier and dimethylacetamide and mix them, add aluminum nitride powder and mix them, then let it stand for 24 hours, take copper sulfate to prepare a saturated solution, add the copper sulfate solution to ultrasonically disperse for 20 minutes, then add zinc powder and heat to 70°C to react for 25 hours, wherein the feed ratio of aluminum nitride powder, surface modifier, copper sulfate, zinc powder and dimethylacetamide is 10g:0.15g:3g:1.9g:35mL, aluminum nitride powder uses Brofos-AlN-W20 type micropowder with an average particle size of 20 microns, finally centrifuge to obtain the precipitate, wash it with hydrochloric acid and water in turn, and obtain the copper-coated substrate after drying.
[0041] Step A3: Place the copper-clad substrate in a nitrogen atmosphere furnace, first bake it at 420°C for 2.7h, then continue to heat it to 840°C and bake it for 1.1h, and then break it up after cooling in the furnace to obtain AlN@Cu micropowder.
[0042] (2) Preparation of coating materials
[0043] The raw materials are taken according to weight percentage, 20wt% of AlN@Cu micropowder is prepared by this embodiment; 4.2wt% of cladding aid is HT40.37 type atomized iron powder; the balance is made up to 100wt% with FeCoNiCrMn high entropy alloy powder, and the particle size distribution is 15-53μm; the raw materials are mixed, added into a grinder for grinding and dispersion, and vacuum dried to obtain a coating material.
[0044] Example 4, preparing a coating material for cemented carbide, the specific implementation process is as follows:
[0045] (1) Preparation of AlN@Cu powder
[0046] Step A1: Dissolve dithiothreitol and acetone under nitrogen protection, then add triallylamine and bis(triphenylphosphine)copper chloride and mix well. Control the temperature of the water bath at 50°C, stir at 150 rpm, and apply 100 W / m 2 The reaction mixture was irradiated with ultraviolet light and the reaction time was controlled to be 7.5 h. The feed ratio of triallylamine, dithiothreitol, bis(triphenylphosphine)copper chloride and acetone was 10 mmol:19 mmol:11 mg:30 mL. After the reaction was completed, acetone was removed to obtain a surface modifier.
[0047] Step A2: Mix the surface modifier and dimethylacetamide, add aluminum nitride powder and mix, and then stand for 24 hours. Take copper sulfate to prepare a saturated solution, add the copper sulfate solution and ultrasonically disperse for 25 minutes, then add zinc powder and heat to 75°C to react for 22 hours, wherein the feed ratio of aluminum nitride powder, surface modifier, copper sulfate, zinc powder and dimethylacetamide is 10g:0.16g:3.1g:2g:40mL, and aluminum nitride powder uses Brofos-AlN-W20 type micropowder with an average particle size of 20 microns. Finally, centrifuge to obtain the precipitate, wash it with hydrochloric acid and water in turn, and dry it to obtain a copper-coated substrate.
[0048] Step A3: Place the copper-clad substrate in a nitrogen atmosphere furnace, first bake it at 400°C for 3 hours, then continue to heat it to 850°C and bake it for 1.1 hours, and then break it up after cooling in the furnace to obtain AlN@Cu micropowder.
[0049] (2) Preparation of coating materials
[0050] The raw materials are taken according to weight percentage, 21wt% of AlN@Cu powder is prepared by this embodiment; 3.8wt% of cladding aid is HT40.37 atomized iron powder; the balance is made up to 100wt% with FeCoNiCrMn high entropy alloy powder, and the particle size distribution is 15-53μm; the raw materials are mixed, added into a grinder for grinding and dispersion, and vacuum dried to obtain a coating material.
[0051] Comparative Example 1, referring to Example 4, the AlN@Cu powder was replaced with the same amount of aluminum nitride powder, and the rest of the implementation process was exactly the same.
[0052] Comparative Example 2, referring to the prior art, adopts chemical copper plating method to prepare AlN-Cu powder and prepare coating material, and the specific implementation process is as follows:
[0053] Step D1: prepare a 10 g / L stannous chloride solution and a 20 g / L hydrochloric acid solution, immerse the aluminum nitride powder twice in sequence, the three immersion times are 10 min and 15 min respectively, wash with ethanol and dry to obtain sensitized micropowder;
[0054] Step D2: sensitized micropowder, disodium ethylenediaminetetraacetate, 2,6-diaminopyridine and copper sulfate solution are mixed, the water bath temperature is controlled at 60°C, and formaldehyde solution is slowly added to react for 1 hour, wherein the feed ratio of sensitized micropowder, disodium ethylenediaminetetraacetate, 2,6-diaminopyridine, copper sulfate and formaldehyde solution is 10g:0.2g:0.08g:3.5g:15mL, the concentration of copper sulfate solution is 10g / L, the mass fraction of formaldehyde solution is 35%, the lower precipitate is centrifuged and dried, and then placed in a nitrogen atmosphere furnace for calcination; the rest of the implementation process is exactly the same as Example 4.
[0055] Take the coating material prepared as above, take YG3X steel as the substrate, and clad the coating material on the substrate surface by laser. The laser cladding parameters are set as follows: laser power 2000W, spot diameter 3mm, scanning rate 100mm / s, and shielding gas flow rate 10L / min;
[0056] The hardness of the coating was tested by a nanoindenter using a continuous loading and unloading method. The friction performance of the coating was tested by a pin-on-disc friction and wear tester. The test pair was an aluminum oxide ball, the normal load was 2N, and the number of friction turns was 3000r. The corrosion resistance of the coating was tested by an electrochemical workstation, and the electrolyte was a 3.5wt% sodium chloride solution. The specific test data are shown in Table 1:
[0057]
[0058] It can be seen from the test results in Table 1 that the coating material prepared in the embodiment maintains good wear resistance after laser cladding, and the corrosion resistance is significantly reduced.
[0059] like Figure 1 , which is an electron microscope image of the AlN@Cu micropowder prepared in Example 4. It can be seen from the image that the AlN@Cu micropowder maintains the initial spherical structure of the AlN powder, and the surface is evenly coated with a copper reduction layer.
[0060] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0061] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A coating material for cemented carbide, characterized in that: The composition is composed of the following components: 17-23wt% AlN@Cu powder and 3.5-4.5wt% cladding additive, and the balance is high entropy alloy powder; The AlN@Cu powder is prepared by the following method: Step A1: Dissolve dithiothreitol and acetone under nitrogen protection, then add triallylamine and bis(triphenylphosphine)copper chloride and mix well, control the temperature in a water bath at 40-50°C, stir and add 80-110W / m 2 The reaction time is controlled to be 6.5-8 hours to obtain a surface modifier; Step A2: dissolving the surface modifier and dimethylacetamide, adding aluminum nitride powder, mixing and standing for 24 hours, then adding copper sulfate solution and ultrasonically dispersing for 15-25 minutes, then adding zinc powder and heating to 60-80°C to react for 20-30 hours, centrifuging and taking the precipitate, washing it with hydrochloric acid and water in turn, and drying to obtain a copper-coated substrate; Step A3: Place the copper-clad substrate in a nitrogen atmosphere furnace, first bake it at 380-440°C for 2.5-3h, then continue to heat it to 820-850°C and bake it for 1-1.3h, and then break it up after cooling in the furnace to obtain AlN@Cu micropowder.
2. A coating material for cemented carbide according to claim 1, characterized in that: The feed ratio of triallylamine, dithiothreitol, bis(triphenylphosphine)copper chloride and acetone is 10mmol:17-20mmol:9-13mg:25-35mL.
3. A coating material for cemented carbide according to claim 2, characterized in that: The feed ratio of aluminum nitride powder, surface modifier, copper sulfate, zinc powder and dimethylacetamide is 10g: 0.14-0.18g: 2.7-3.3g: 1.6-2.1g: 30-40mL.
4. A coating material for cemented carbide according to claim 3, characterized in that: Aluminum nitride powder is micron-sized powder with an average particle size of no more than 20 μm.
5. The coating material for cemented carbide according to claim 1, characterized in that: The high entropy alloy powder is one of FeCoNiCrTi alloy powder and FeCoNiCrMn alloy powder.
6. The coating material for cemented carbide according to claim 1, characterized in that: The particle size of the high entropy alloy powder is 10-60 μm.
7. The coating material for cemented carbide according to claim 1, characterized in that: The cladding aid is atomized iron powder.
8. A method for preparing a coating material for cemented carbide according to any one of claims 1 to 7, characterized in that: Specifically, the raw materials are mixed, dry-ground and dispersed, and vacuum-dried to obtain the coating material.
Citation Information
Patent Citations
Copper-plating graphite composite material and preparation method thereof
CN101230456A
Copper-based powder metallurgy friction material containing nitride and preparation method thereof
CN117620158A